Elevated monocyte to high-density lipoprotein cholesterol ratio correlates with clinical severity in acute inflammatory demyelinating polyradiculoneuropathy patients - Peng, You-Fan; Luo, Miao; Zhang, Qing-Song (Frontiers in Neurology, 2022)
Monocyte to high density lipoprotein-cholesterol ratio (MHR) has been reported to be associated to nervous system lesion, the role of MHR has not been determined in patients with Guillain-Barré Syndrome (GBS). The purpose of our study was to explore the role of MHR in patients with GBS. A total of 52 GBS patients were involved in the study retrospectively, including acute inflammatory demyelinating polyradiculoneuropathy (AIDP), acute motor axonal neuropathy (AMAN) and acute motor sensory axonal neuropathy (AMSAN). We used Hughes Functional Grading Scale (HFGS) score to evaluate functional status in GBS patients. Among patients with different subtypes of GBS, MHR was significantly elevated in those with demyelination compared to patients without demyelination (p＜0.001), AIDP patients had an increased MHR compared with AMAN or AMSAN patients (p=0.001;p=0.013). There was a positively correlation between MHR and HFGS score (r =0.463, p=0.006) in AIDP patients, but not in AMAN or AMSAN. Multiple linear regression analysis revealed that MHR was independently associated with HFGS score (beta=0.405, p=0.013) in AIDP patients. Our study suggests that MHR as an inflammatory marker is elevated in patients with AIDP compared to AMAN or AMSAN patients, MHR is positively clinical severity in AIDP patients, suggesting that MHR may provide an additional information to reflect the pathophysiology of AIDP.